A study of why some physic concepts in the South African Physical Science curriculum are poorly understood in order to develop a targeted action-research intervention for Newton's second law - Cobbing, Kathleen Margaret (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2020)
Globally, many students show a poor understanding of concepts in high school physics and lack the necessary problem-solving skills that the course demands. The application of Newton's second law was found to be particularly problematic through document analysis of South African examination feedback reports, as well as from an analysis of the physics examinations at a pair of well-resourced South African independent schools that follow the Independent Examination Board curriculum. Through an action-research approach, a resource for use by students was designed and modified to improve students' understanding of this concept, while modelling problemsolving methods. The resource consisted of brief revision notes, worked examples and scaffolded exercises. The design of the resource was influenced by the theory of cognitive apprenticeship, cognitive load theory and conceptual change theory. One of the aims of the resource was to encourage students to translate between the different representations of a problem situation: symbolic, abstract, model and concrete. The impact of this resource was evaluated at a pair of schools using a mixed methods approach. This incorporated pre- and post-tests for a quantitative assessment, qualitative student evaluations and the analysis of examination scripts. There was an improvement from pre- to post-test for all four iterations of the intervention and these improvements were shown to be significant. The use of the resource led to an increase in the quality and quantity of diagrams drawn by students in subsequent assessments.
Keywords: Physics -- Study and teaching (Secondary) -- South Africa; Physics -- Examinations, questions, etc. -- South Africa; Motion -- Study and teaching (Secondary) -- South Africa